Future libraries - Bloch, R. Howard; Hesse, Carla Alison (Representations books, 1995)
As the digital revolution sweeps us toward the twenty-first century, what issues, passions, and anxieties are evoked when we consider the place of the library in the future? Humanists and social scientists are only beginning to recognize that the current revolution in the dissemination of knowledge is comparable to the one that followed the advent of printing, when huge numbers of books first became available. On the eve of the opening of the Bibliothèque de France, which has become a lightning rod for the issues raised by the electronic revolution, this collection brings together distinguished lawyers, historians, librarians, computer scientists, linguists, and architects to assess the future of libraries, books, and the printed word. The contributors represent a wide range of institutions: the Bibliothèque de France, the Library of Congress, law schools, architectural firms, universities. We are still exploring the ramifications of revolutionary techniques for writing and reading; new modes of storing and distributing data; new possibilities for acquiring, reconfiguring, and integrating knowledge. 'Future libraries' does much to stimulate and inform the debate on a revolution that will affect our most diverse cultural forms and our deepest social structures.